Pattern of Eprinomectin Milk Excretion in Dairy Sheep Unaffected by Lactation Stage: Comparative Residual Profiles in Dairy Products - Imperiale, Fernanda Andrea (2006)
Eprinomectin (EPM) is a broad-spectrum endectocide compound approved for use in dairy cattle with a zero milk-withdrawal period, but has not been registered for use in lactating dairy sheep. The pattern of EPM excretion in milk was comparatively characterized following its pour-on administration (500 microg/kg) to lactating dairy sheep at two different stages of lactation. The relationship between milk excretion and plasma disposition kinetics of EPM was characterized. Residual EPM concentrations were assessed during cheese making (whey and curd) and ripening (cheese) by high-performance liquid chromatography and fluorescence detection. EPM was poorly distributed from the bloodstream to the mammary gland and low concentrations were excreted in milk. The level of milk production (early-mid and mid-late lactation) did not affect either the plasma-milk distribution or the pattern of residual concentrations in milk. During cheese making, the highest residual concentrations of EPM were measured in the curd, which increased during cheese ripening, reaching a maximum after 40 days. However, these residual concentrations were below the maximum residue limit of 20 ng/ml established for EPM in bovine´s milk. Therefore, these dairy products could be considered safe for consumers after the EPM antiparasitic pour-on treatment (500 microg/kg) in lactating dairy sheep.